2010
DOI: 10.1021/ef901231j
|View full text |Cite
|
Sign up to set email alerts
|

Selective Production of Aromatics by Crude Bio-oil Valorization with a Nickel-Modified HZSM-5 Zeolite Catalyst

Abstract: The transformation of crude bio-oil to hydrocarbons has been studied in an online thermal catalytic process that is comprised of two steps: the thermal treatment reactor, followed by the catalytic reactor. The deposition of pyrolytic lignin formed by the polymerization of biomass-derived products is enhanced in the thermal step. Volatiles are processed in a fluidized-bed reactor with a catalyst that is hydrothermally stable and selective for aromatic production, which is based on a HZSM-5 zeolite modified by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
126
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(140 citation statements)
references
References 50 publications
5
126
0
3
Order By: Relevance
“…Thermal coke was formed by condensation-degradation and polymerization reactions of bio-oil oxygenated compounds derived from lignin pyrolysis in step A [76]. The methanol and bio-oil mixture was transformed into aromatic hydrocarbons present in the hydrocarbon pool via direct deoxygenation, dehydration, decarboxylation, decarbonylation, and cracking reactions using a Ni/HZSM-5 catalyst in step B [79]. Some hydrocarbons contained in the hydrocarbon pool were transformed to C 2-4 olefins through oligomerization-cracking reactions in step C [80].…”
Section: Reducing Catalyst Deactivation In Catalytic Crackingmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermal coke was formed by condensation-degradation and polymerization reactions of bio-oil oxygenated compounds derived from lignin pyrolysis in step A [76]. The methanol and bio-oil mixture was transformed into aromatic hydrocarbons present in the hydrocarbon pool via direct deoxygenation, dehydration, decarboxylation, decarbonylation, and cracking reactions using a Ni/HZSM-5 catalyst in step B [79]. Some hydrocarbons contained in the hydrocarbon pool were transformed to C 2-4 olefins through oligomerization-cracking reactions in step C [80].…”
Section: Reducing Catalyst Deactivation In Catalytic Crackingmentioning
confidence: 99%
“…C 2-4 olefins were then transformed to C 5+ aliphatics and C 5+ aromatics through alkylation, oligomerization and hydrogen transfer reactions in step D [81]. The C 5+ aliphatics and C 5+ aromatics then undergo rearrangement and condensation reactions to form alkylaromatics and polyaromatics that comprise the catalytic coke in step E [77,79]. Some hydrocarbons present in the hydrocarbon pool were directly converted to catalytic coke through oligomerization, cyclization, aromatization, and condensation reactions that were catalyzed by acid sites of Ni/HZSM-5 catalyst in step F [76].…”
Section: Reducing Catalyst Deactivation In Catalytic Crackingmentioning
confidence: 99%
“…Besides, some thermally sensitive compounds, such as pyrolitic lignin, might undergo aggregation to form a precipitate, which would block the reactor and lead to deactivation of the catalyst. Consequently, efforts have been made to avoid this phenomenon by separating these compounds through thermal pre-treatment (Valle et al, 2010). Therefore, to maintain the stability and high performance of the cracking process, it is necessary to obtain fractions suitable for cracking by separation of bio-oil, to achieve the partial conversion of bio-oil into hydrocarbon fuels.…”
Section: The Importance Of Separation Technologymentioning
confidence: 99%
“…However, direct cracking of bio-oil faces problems of low aromatic hydrocarbon yield and severe coking (Vitolo et al 1999). There are two main reasons for the coke (carbonaceous deposit) formation: the presence of large molecular weight compounds in bio-oil, such as phenolic oligomers (pyrolytic lignin), which are nonvolatile and have low cracking reactivity, resulting in easy carbonaceous deposition in the catalytic bed (Valle et al 2010); and the hydrogen-poor composition, namely the high unsaturation degree that leads to the low integral H/C ratios of final products and also favors the formation of coke (Zhang et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, because the hydrogenlacking property of this fraction is not improved, proper hydrogen supply is still required to adjust the H/C ratio of the final products. Researchers found that by coprocessing with hydrogen-rich chemicals, such as alcohols, the cracking behaviors of bio-oil components could be improved (Valle et al 2010;Mentzel and Holm 2011). In the authors' previous studies alcohols were also introduced as the coreactants (Wang et al 2012a(Wang et al , 2013aWang et al 2014b).…”
Section: Introductionmentioning
confidence: 99%